2022
DOI: 10.1186/s13690-022-00812-7
|View full text |Cite
|
Sign up to set email alerts
|

Geotemporospatial and causal inferential epidemiological overview and survey of USA cannabis, cannabidiol and cannabinoid genotoxicity expressed in cancer incidence 2003–2017: part 2 – categorical bivariate analysis and attributable fractions

Abstract: Background As the cannabis-cancer relationship remains an important open question epidemiological investigation is warranted to calculate key metrics including Rate Ratios (RR), Attributable Fractions in the Exposed (AFE) and Population Attributable Risks (PAR) to directly compare the implicated case burden between emerging cannabinoids and the established carcinogen tobacco. Methods SEER*Stat software from Centres for Disease Control was used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 128 publications
11
40
0
Order By: Relevance
“…The full implications of this profound and far-reaching result have yet to be fully explored. They have an obvious relevance and concordance with the results reported both in this study and in similar reports [27,[79][80][81][96][97][98]. Several classical studies have provided clear evidence of chromosomal breaks [9,10,13], end-to-end fusions [9,10], and chromosomal bridge formations in telophase [11,12,99] following cannabis exposure.…”
Section: Recent Dna Methylation Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…The full implications of this profound and far-reaching result have yet to be fully explored. They have an obvious relevance and concordance with the results reported both in this study and in similar reports [27,[79][80][81][96][97][98]. Several classical studies have provided clear evidence of chromosomal breaks [9,10,13], end-to-end fusions [9,10], and chromosomal bridge formations in telophase [11,12,99] following cannabis exposure.…”
Section: Recent Dna Methylation Studiessupporting
confidence: 92%
“…The link between cancer and cannabinoids is complex and multifactorial and has recently been reviewed in several recently published works [10,[14][15][16]27,31,32,34,35,[41][42][43]71,72,75,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. Our intention here is to introduce the way in which these general observations may relate to some specific cancer types.…”
Section: Mechanisms Of Cannabinoid Carcinogenesismentioning
confidence: 99%
“…There are indications that in these areas large crops of cannabis are being cultivated and food chain contamination seems likely. Since epidemiological studies have confirmed that the exponentiation of cannabinoid genotoxicity seen in the laboratory is also reflected in patterns of congenital anomaly incidence [ 1 , 3 , 4 , 8 , 22 , 23 , 24 , 25 ] a relatively abrupt rise in community cannabinoid exposure would be expected to be associated with a relatively sudden and abrupt step-wise rise in congenital anomaly rates. This issue seems to not be well understood in the public health community.…”
Section: Introductionmentioning
confidence: 99%
“…The concern is that this relatively abrupt launching of parts of the continent into higher cannabinoid exposure zones will continue to see an increasing number of severe genotoxic outcomes such as those described above for amelia. Particularly when this report is read in conjunction with other reports on cannabinoid teratogenicity [ 4 , 5 , 6 , 7 , 11 , 16 , 108 , 130 , 131 ], cannabinoid cancerogenicity [ 95 , 96 , 97 , 99 , 100 , 102 , 103 , 104 , 106 , 108 ], cannabinoid accelerated aging [ 102 , 132 , 133 ], heritable mutagenic and carcinogenic disease [ 98 , 99 , 100 , 108 , 134 , 135 , 136 ], and heritable neurotoxicity [ 107 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ], it becomes clear that rational policies in this area would tightly restrict and control community exposure to genotoxic and neurotoxic cannabinoids for multiple public health indications as has always been the community’s response to known serious genotoxic xenobiotics. The prospect of continued contamination of the food chain and increasing population exposure, incurring avoidable genetic and epigenetic damage to the heritable material of the population for multiple generations to come, is most serious indeed.…”
Section: Discussionmentioning
confidence: 94%
“…As outlined in the introduction, the mechanisms of cannabis genotoxicity are many and complex and have been reviewed elsewhere [ 4 , 5 , 6 , 7 , 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. For our present purposes, we wish to focus on two pathways of particular importance, these being the disruption of key morphogen gradients and the epigenomic perturbations.…”
Section: Discussionmentioning
confidence: 99%